Peer effects in the valuation of attributes and practices for food safety: findings from the study of dairy consumers in India - Chandra, Raj; Munasib, Abdul; Roy, Devesh; Sonkar, Vinay Kumar (International Food Policy Research Institute, 2015)
Food safety is an integral part of food security. One of the ways of ensuring food safety is through demand pull by consumers, which depends on the information available to them. One of the possible ways in which information is available to consumers is through their social networks. Focusing on dairy consumers in India, we present evidence of peer effects in consumers’ attitudes toward various food safety attributes as well as food safety practices. Unobserved individual heterogeneities are crucial confounders in the identification of social (endogenous) effects. Our identification is based on exploiting within-consumer variation across different aspects of attitude (or practices) related to food safety.